Community paramedic outreach support for people experiencing homelessness. (2nd February 2023) - Taplin, John; Dalgarno, Dana; Smith, Michele; Eggenberger, Ty; Ghosh, Sumantra Monty
Abstract : Objective: To evaluate the implementation phase of a community paramedic program focused on individuals experiencing homelessness (IEH) in Calgary, Alberta, Canada with a high prevalence of mental health and substance use disorders. Methods: A manual chart review was performed to characterise patients of the City Centre Team (CCT). A survey was performed of health professionals and partners for allied agencies that interacted with the CCT in the first 6 months of program implementation. Findings: There were 832 patient events involving 365 unique patients. Mental health and substance use disorders accounted for 75% of the events. The survey results were positive with 85% agreeing that the CCT reduced the reliance on emergency services. Conclusion: The community paramedics address the health and social needs of IEH while working in a multidisciplinary setting. The CCT is an innovative program that can inform future health service design in similar settings.